ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2017-2020 - kadari, kadari; Supardi, Supardi (PRIMA EKONOMIKA, 2023)
This study aims to obtain empirical evidence has a significant effect of profitability, company size, Social Responsibility and capital structure on the value of the company either partially or simultaneously. The results of that profitability has a significant effect on the value of the company, the size of the company has no significant effect on the value of the company, Social Responsibility has a significant effect on the value of the company, As for the capital structure has no significant effect on the value of the company, The results of the F test showed that profitability, company size, Social Responsibility, and capital structure simultaneously significantly affect the value of the company.The coefficient of determination test results obtained a value of 0.242 or 24,2%. This shows that profitability, company size, Social Responsibility and capital structure only 24,2% affect the value of the company and the remaining 75,8% are influenced by other variables. Keywords : Profitability, Company Size, Social Responsibility, Capital Structure, Corporate Value